2015
DOI: 10.1007/s10709-015-9853-2
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic chromosome configurations in triploid progeny from reciprocal crosses between wild-type diploid and natural tetraploid loach Misgurnus anguillicaudatus in China

Abstract: Here, we showed meiotic chromosome configurations prepared from oocyte germinal vesicles and spermatocytes of triploid loaches produced from reciprocal crosses between wild-type diploids (2n = 50) obtained from Dalian, Liaoning Province, China and natural tetraploids (4n = 100) from Chibi, Hubei Province, China. Major meiotic cells in triploids comprised 25 bivalents and 25 univalents, but cells with one to five trivalents were also observed. When three homologous chromosomes bearing nucleolar organizing regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…22IIs ? 3IIIs and so on (Li et al 2015). In our previous study, we also reported failure of synapsis between homologues and thus formation of gametes with unbalanced genetic materials was also predicted (Li et al 2015).…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…22IIs ? 3IIIs and so on (Li et al 2015). In our previous study, we also reported failure of synapsis between homologues and thus formation of gametes with unbalanced genetic materials was also predicted (Li et al 2015).…”
Section: Discussionmentioning
confidence: 67%
“…3IIIs and so on (Li et al 2015). In our previous study, we also reported failure of synapsis between homologues and thus formation of gametes with unbalanced genetic materials was also predicted (Li et al 2015). Hamphrey (1950, 1954) observed a shift toward the lower chromosome numbers in diploid 9 triploid axolotl progenies and suggested that this was caused by the elimination of some lagging chromosomes and the resultant failure of gametogenesis in gametes with higher numbers of extra chromosomes.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations